Understanding the Needs of Australian Carers of Adults Receiving Palliative Care in the Home: A Systematic Review of the Literature - Elizabeth M. Miller BN (Hons.); Joanne E. Porter PhD, MN, Grad Dip CC, Grad Cert Ed, Grad Dip HSM, BN, RN (SAGE Publishing, 2021)
Introduction Caring for someone at home requiring palliative care is an ominous task. Unless the current support systems are better utilised and improved to meet the needs of those carers, the demand for acute hospital admissions will increase as the Australian population ages. The aim of this review was to examine the needs of unpaid carers who were caring for adults receiving palliative care in their home in Australia. Methods: A systematic review of the literature was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines between 2008-2020. Results: Only Australian papers were selected due to the intent to understand carers' needs in the Australian context and 17 papers made up the final data set. Four themes emerged: 1) Perceived factors influencing caregiving; 2) Perceived impact and responses to caregiving; 3) Communication and information needs; and 4) Perceptions of current palliative support services and barriers to uptake. Conclusion: Carers reported satisfaction and positive outcomes and also expressed feeling unprepared, unrecognised, stressed and exhausted.